Enrichment, Source Apportionment and Health Risk Assessment of Soil Potentially Harmful Elements Associated with Different Land Use in Coastal Tidelands Reclamation Area, Eastern China - Chen, Xinjian (Int J Environ Res Public Health, 2020)
Coastal tidelands are important ecological habitat resources and valuable resources for agricultural land reclamation. Enrichment of potentially harmful elements (PHEs) in soil caused by anthropogenic activity is an important factor implicated in the ecological deterioration of soil in China. A total of 54 soil sample sites were selected from a 30-year reclaimed tideland and an adjoining coastal wetland. Descriptive and multivariate statistical analyses were performed to describe the enrichment, source, health risk status of eight PHEs (As, Co, Cr, Cu, Mn, Ni, Pb, and Zn) after long-term reclamation. Results indicated that after 30 years of reclamation, most soil PHEs are slightly enriched, whereas no serious threat of environmental pollution was observed. In the reclamation area, the enrichment of PHEs in the aquaculture land, industrial land, and cropland was relatively high compared with other land use types, such as tideland and halophyte land. The source analysis divided the PHEs into five categories: (1) Cu; (2) Co and Mn; (3) Cr; (4) As and Pb; (5) Zn and Ni. Cu was completely derived from natural parent materials and other elements were governed by both weathering of parent rock and human activities, including agricultural activities, industrial production, and transportation emissions. The health risk assessment showed that the soil PHEs potentially had no non-carcinogenic risk to the public, but there was an acceptable probability to have cancer due to Cr and As. Meanwhile, children are more susceptible to harm from the PHEs in soil than adults. According to the economic and social development situation in the coastal region, it is necessary to pay attention to the environmental threats of PHEs enrichment.